Teachers’ Professional Development, Teachers'quality and Students’ Academic Achivements in the Public-Private Partnership Schools - Tinuola, Oladosu, Christianah; Adeola, Ayoola, Rebecca; Olusola, Olokede, Nathanel; Omolola, Ojo, Adeola (Current Research in Language, Literature and Education Vol. 4, 2022)
Public Private Partnership (PPP) has become a virile tool for providing public service and developing society in both developed and developing countries and it has worked in many countries of the world, including Senegal, the United Kingdom, and the United Arab Emirates. These countries have built huge infrastructures and edifices through PPP deals. However, it is yet to work in Nigeria. Therefore, the present study assesses teachers’ professional development, teachers'quality and students’ academic achievements in the PPP and non-PPP schoqols. The objective of the study is to find out the level of professional development of teachers, teacher’s quality (qualification, years of experience) and its influence on student’s academic achievement. The study adopts quasi-experimental pre-test and post-test control group design with one experimental groups and control group. Population for this study consists of all senior secondary school class I students in Osun state. A total sample of 1312 subjects (1152 SS 2 Students and 160 SS Teachers) were selected with the use of multistage sampling technique. Research instruments used for this study include: (i) English Achievement Test (EAT) r=0.78; (ii) Mathematics Achievement Test (MAT) 0.65; and (iii). Teachers’ Quality Inventory (TQI) r= 0.72. The procedure for the study was in stages, the pre-treatment stage and the post-treatment stage. The data were analyzed using descriptive and inferential statistics, the hypotheses generated in this study were tested at 0.05 level of significance. The result revealed thatteachers are more efficient after going through a professional program. In conclusion, If high standardwill be maintained as regards students outcomesthere is the need improve on the teachers' professional development. It was therefore recommended that teachers should be encouraged to attend relevant workshops, seminars, on the job trainings regularly. Moreover, due to recent pandemic of different versions of Coronavirus, Webinars and Zoom (Virtual mode) meetings are now available in different fields of learning and these are opportunities for classroom teachers to acquire professional developmental trainings without having physical attendance.